Design and Applications of Tumor Microenvironment-Responsive Nanogels as Drug Carriers - Du, Xinjing; Gao, Yuting; Kang, Qi; Xing, Jinfeng (Frontiers in Bioengineering and Biotechnology, 2021)
In recent years, the exploration of tumor microenvironment has provided a new approach for tumor treatment. More and more researches are devoted to designing tumor microenvironment-responsive nanogels loaded with therapeutic drugs. Compared with other drug carriers, nanogel has shown great potential in improving the effect of chemotherapy, which is attributed to its stable size, superior hydrophilicity, excellent biocompatibility and responsiveness to specific environment. This review primarily summarizes the common preparation techniques of nanogels (such as free radical polymerization, covalent cross-linking, and physical self-assembly) and loading ways of drug in nanogels (including physical encapsulation and chemical coupling) as well as the controlled drug release behaviors. Furthermore, the difficulties and prospects of nanogels as drug carriers are also briefly described.